A study of the press-and-chop technique in cataract surgery training - XU Mao; QI Yongjun; YANG Yang; DENG Jianhua; LIU Wanjun; YE Xiangxiang; MO Ting (Yanke Xuebao)
[Objective] To investigate the effect of the press-and-chop technique in cataract phacoemulsification training. [Methods] From January 2019 to December 2023, 30 trainees who studied cataract phacoemulsification surgery in the ophthalmology department of Guangdong Hospital of Traditional Chinese Medicine,Zhuhai were selected as the research subjects. The training period for all subjects was 3 months, and they were divided into two groups: phaco-chop teaching group and press-and-chop teaching group. The quantity of porcine eye surgeries performed by each trainee before completing the first nuclear chopping, the quantity of porcine eye surgeries performed before completing all surgical steps for the first time, and the number of times of complete nuclear chopping in one attempt were recorded. At the end of the training, the trainees were assessed on their ability to perform porcine eye surgeries and their scores were recorded. A questionnaire survey was conducted to valuate the two teaching methods. [Results] The average number of porcine eye surgeries performed by the press-and-chop teaching group before completing the first nuclear chopping was 36.69 (19, 50), which was lower than the phaco chop teaching group's 49.86 (29,66);The average number of porcine eye surgeries performed by the press-and-chop teaching group before before the first completion of all surgical steps was 58.13 (31, 79), which was lower than the phaco chop teaching group's 73.14 (50, 90).The average number of complete nuclear chopping in one attempt in the press-and-chop teaching group was 14.75 (9, 22), which was higher than the phaco chop teaching group's 6.79 (3, 14);The average score of the chopping step of porcine eye surgery for the press-and-chop teaching group was 4.50 (3, 5), which was higher than the phaco chop teaching group's 3.71 (2, 5);The average score for the press-and-chop teaching group of the complete surgery examination was 29.00 (23, 33), which was higher than the phaco chop teaching group's 23.07 (19, 28).At the end of the training, the average score of the survey questionnaire on the evaluation of teaching effectiveness by the press-and-chop teaching group was 18.31 (15, 20),which was higher than that of the phaco chop, which was 15.07 (12, 18). [Conclusions] The press-and-chop technique helps trainees to master the chopping technique faster, shorten the learning curve of cataract phacoemulsification surgery, enhance confidence in learning cataract surgery, and improve the teaching effectiveness and satisfaction of cataract phacoemulsification surgery.